Understand the underlying structure of the determinants of overall job performance evaluation - saad ali alanezy; amer ali alatawy (Iraqi Journal for Administrative Sciences, 2025)
The present research aims to explore content nature of latent structure of antecedents of overall job performance ratings based upon previous researchers\\' notions and opinions in explaining comprehensive multi view for job performance dimensions. This view agrees that job performance for employee includes three main dimensions (task performance, citizenship performance and counterproductive work behavior). Conceptual and empirical purport for this research depend on three key directions. The first direction proceeds to knowing relationship nature among three performance dimensions and overall job performance ratings. The second direction aims to explore relative importance for these dimensions on overall job performance ratings. In the third direction, this research attempts to know interrelationships among these three dimensions. By using structural equation modeling, the research\\'s hypotheses were tested and some of meaningful recommendations were formulated.